বাংলাদেশের মক্তিযুদ্ধ, পত্রিকাপঞ্জি - আজাদ, কুতুব 1973-; মন্তাজ, সাহেদ 1973- (ঢাকা : বাংলা একাডেমী ঢাকা, 2008)
Index to articles on the liberation war of Bangladesh as reflected in 1971, in contemporary English newspapers published from various countries of the world.
Bengali and English.
Keywords: Bangladesh -- History -- Revolution, 1971 -- Press coverage -- Indexes; Bangladesh -- History -- Revolution, 1971 -- Foreign public opinion